INTERPRETATION OF INTELLIGENCE ASSETS AND LIABILITIES REPORT FROM THE SHORT AND LONG TERM - Garcia, Victor (2005)
In this study the intellectual function expressed in Aristotle 's Tratado delalma is related to modern conceptualization on the nmemic system. Thedifferences between the Agent and the Patient are described, and adiscussion on cognitive theory considering long and short-term memoryensues. The discussion ends when pointing at similarities and differencesbetween both paradigms.